2022
DOI: 10.1007/s11606-022-07419-2
|View full text |Cite
|
Sign up to set email alerts
|

Systems on Top of Nasal Cannula Improve Oxygen Delivery in Patients with COVID-19: a Randomized Controlled Trial

Abstract: BACKGROUND: Treating hypoxemia while meeting the soaring demands of oxygen can be a challenge during the COVID-19 pandemic. OBJECTIVE: To determine the efficacy of the surgical facemask and the double-trunk mask on top of the lowflow oxygen nasal cannula on arterial partial pressure of oxygen (PaO 2 ) in hypoxemic COVID-19 patients. DESIGN: Randomized controlled trial. PARTICIPANTS: Hospitalized adults with COVID-19 and hypoxemia treated with the low-flow nasal cannula were enrolled between November 13, 2020, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…Poncin et al 1 found that compared with the NC alone, addition of the surgical face mask or the DTM above the NC improved patient arterial oxygenation. The vital parameters as well as the degree of breathlessness, however, did not differ among the groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Poncin et al 1 found that compared with the NC alone, addition of the surgical face mask or the DTM above the NC improved patient arterial oxygenation. The vital parameters as well as the degree of breathlessness, however, did not differ among the groups.…”
Section: Resultsmentioning
confidence: 99%
“…All patients with hypoxaemia requiring low-flow oxygen therapy between 3 and 7 L/min with an NC to maintain peripheral capillary oxygen saturation (SpO2) between 92% and 96% were randomised in a 1:1:1 ratio to receive oxygen therapy via three different methods. Either an NC alone (control) or the NC covered by the surgical face mask or the DTM was used to deliver oxygen 1…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation